2018
DOI: 10.1007/s12325-018-0796-8
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Overactive Bladder and Falls and Fractures: A Systematic Review

Abstract: IntroductionUrinary symptoms are associated with an increased risk of falls, but few studies have focused on patients with overactive bladder (OAB). This study aimed to synthesize estimates of the risk of falls and fractures in patients with OAB.MethodsMedline, EMBASE, the Cumulative Index to Nursing and Allied Health Literature, and Scopus were systematically searched for observational studies that focused on patients with OAB. When available, data from a non-OAB comparison sample were included. Double indepe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
38
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 59 publications
1
38
0
1
Order By: Relevance
“…Care must also be used in interpreting the findings, as the study involved community‐dwelling older women and men with complex needs which may limit generalizability to their healthier counterparts. Lastly, continence management strategies, including pharmacotherapy for OAB, have yielded little evidence for falls reduction to date 13,28 . Indeed, the increased falls risk associated with anticholinergic medications may offset the benefits of these continence management strategies in decreasing falls in this population 13,28 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Care must also be used in interpreting the findings, as the study involved community‐dwelling older women and men with complex needs which may limit generalizability to their healthier counterparts. Lastly, continence management strategies, including pharmacotherapy for OAB, have yielded little evidence for falls reduction to date 13,28 . Indeed, the increased falls risk associated with anticholinergic medications may offset the benefits of these continence management strategies in decreasing falls in this population 13,28 .…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, continence management strategies, including pharmacotherapy for OAB, have yielded little evidence for falls reduction to date 13,28 . Indeed, the increased falls risk associated with anticholinergic medications may offset the benefits of these continence management strategies in decreasing falls in this population 13,28 . Although a large recent US population‐based retrospective study demonstrated that falls risk was lower for older adults who had received treatment (pharmacological, surgical, or both) for OAB compared with OAB patients who did not receive such treatment 29 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…OAB is a symptom complex that may significantly impact sufferers' quality of life including their physical and mental health, social, sexual, economical and professional lives 17,18 . Idiopathic OAB is a symptom-based diagnosis, however, a consensus regarding the symptom severity or combination necessary for accurate OAB diagnosis is lacking.…”
Section: Discussionmentioning
confidence: 99%
“…The sphincter muscle is also important for bladder and bowel management. The pelvic floor muscle (PFM) is associated with sphincter and supports the abdominal viscera from the pelvic floor 32,36) . The passenger unit during post-stroke gait consists of the PFM, TrA, multifidus muscle, and the diaphragm.…”
Section: Discussionmentioning
confidence: 99%